In Vitro Study of Light Radiation Penetration Through Dentin, According to the Wavelength - Dogandzhiyska Violeta (Sciendo, 2015)
Based on their biological, analgesic and antibacterial effect, lasers are becoming more widely used in clinical practice in the recent years. In order to obtain a therapeutic effect and to prevent dental pulp alteration in the treatment of hard tooth tissue, the parameters of laser radiation should be precisely controlled. Upon irradiation of dental pulp, these effects are dependent on the permeability of light through the enamel and dentin. The purpose of our study was to examine the penetration of light through dentin, according to the wavelength.The absorption of light was also studied. For the aim of our investigation 30 dentin samples with thickness 1 mm of extracted human teeth (premolars and molars) were prepared. The absorption and transmission of light in the range 350-1000 nm in its passage through the samples were studied using a spectrophotometer Ocean Optics QE65000. The obtained results showed that the light absorption of dentin in spectral range 350-600 nm depends on the wavelength. When light sources, emitting in the wavelength range above 600 nm were used, the dependence was low. These features should be taken into account in the choice of irradiation wavelength and a light source.